Product Service Diversification Strategy to Increase Revenue and Maintain Financial Stability of Restu Ibu Hospital Balikpapan - Tommy Hendrawan; A. Rohendi; Yuniati Lestari (Research of Service Administration Health and Sains Healthys, 2025)
This study aims to develop a service diversification model to enhance the financial stability of Restu Ibu Hospital in Balikpapan, which faces high dependence on BPJS Health payments (69.3% of revenue). A qualitative method with focused interviews and SWOT analysis was employed to identify challenges and opportunities for diversification. Results show that reliance on BPJS causes liquidity risks due to delayed claims, limited budget allocation for development, and competition from new hospitals. Recommended services include corporate clinic management, medical check-ups, home care, telemedicine, and technology-based premium services. The SWOT analysis highlights the importance of leveraging internal resources (subspecialist doctors, investor networks) and mitigating weaknesses (HR, outdated facilities). A phased implementation strategy is proposed, covering technology enhancement (Hospital Information System, patient apps), staff training, and aggressive marketing to reduce BPJS dependency to ≤50% within 5 years. The study concludes that innovation-driven service diversification improves financial stability and competitiveness in a dynamic healthcare industry.